Experience with Prosthetic Valve Replacement in Indigents with Rheumatic Heart Disease in Nigeria: 10-Year Follow-Up - Nwiloh, Jonathan O.; Oludara, Mobolaji A.; Adebola, Phillip A.; Edaigbini, Sunday A.; Danbauchi, Solomon (Scientific Research, 2015)
Purpose: Active heart surgery programs are few in sub Saharan Africa outside of South Africa, with majority being low volume centers performing small numbers annually. We reviewed our long term outcome to identify factors associated with increased morbidity and mortality, to guide future choice of prosthetic valves in our mostly indigent patients afflicted with rheumatic valvular disease. Methods: Retrospective analysis of patients who underwent heart valve replacement at Lagos State University and Ahmadu Bello University Teaching Hospitals from November 2004 to February 2009. Results: Twenty six patients, 19 (73.1%) females, age 12 - 47; mean 26.69 ± 9.87 years, underwent heart valve replacement. 19 (73.1%) patients had mitral and 7 (26.9%) aortic valve replacement. Mechanical valve was implanted in all except in 2 (7.7%) patients. Left ventricular ejection fraction was >50% in 14 (53.8%), 24 (92.3%) were in New York Heart Association class III/IV, 10 (38.5%) had severe pulmonary hypertension and logistic euroscore was 5.84 ± 3.81. Operative mortality was 11.5% (3/26) and morbidity 7.7% (2/26). Follow-up for survivors was 83.0 ± 27.9 months. 10-year freedom from bleeding and thromboembolism was 70.0% and survival 86.0%. Linearized rate for bleeding was 4.58 and thromboembolism 1.52. Conclusion: Late complications in survivors were primarily anticoagulant related occurring predominantly in child bearing age females especially during pregnancy. Bleeding complications were often associated with noncompliance due to poor socioeconomic status. With average life expectancy of 53 years for females, bioprosthetic valves despite higher structural failure rate, may be best suited especially in child bearing age females still desirous of childbirth to decrease valve related complications. Longer duration of follow-up and meta-analysis of future reported series from the subregion may help clarify the optimal prosthetic valve in sub Saharan Africa with its known poor health infrastructures and delivery system.
Keywords: Rheumatic Valve Disease; Prosthetic Valve; Anticoagulation Complications